2019
DOI: 10.1364/boe.10.001207
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography-guided laser marking with tethered capsule endomicroscopy in unsedated patients

Abstract: Tethered capsule endomicroscopy (TCE) is an emerging screening technology that comprehensively obtains microstructural OCT images of the gastrointestinal (GI) tract in unsedated patients. To advance clinical adoption of this imaging technique, it will be important to validate TCE images with co-localized histology, the current diagnostic gold standard. One method for co-localizing OCT images with histology is image-targeted laser marking, which has previously been implemented using a driveshaft-based, balloon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Early TCE studies showed feasibility without significant adverse events 13,14 . The recent addition of a laser marking system should allow studies to evaluate for histopathologic correlation to TCE images 15 . Currently, this technology is not commercially available.…”
Section: Tethered Capsule Endomicroscopymentioning
confidence: 99%
“…Early TCE studies showed feasibility without significant adverse events 13,14 . The recent addition of a laser marking system should allow studies to evaluate for histopathologic correlation to TCE images 15 . Currently, this technology is not commercially available.…”
Section: Tethered Capsule Endomicroscopymentioning
confidence: 99%
“…A capsule in 2015 was able to combine en face and circumferential luminal scanning to obtain large field coverage (30 cm2) and small field inspection (1 cm2), yielding both volumetric and en face imaging [124]. A more recent capsule paper [131] also incorporated laser marking into tethered capsule endomicroscopy (TCE). Laser marking is a way of co-localizing OCT images with histology [131] (120), and the laser marks had a spatial accuracy of better than 0.5 mm.…”
Section: Capsulementioning
confidence: 99%
“…A more recent capsule paper [131] also incorporated laser marking into tethered capsule endomicroscopy (TCE). Laser marking is a way of co-localizing OCT images with histology [131] (120), and the laser marks had a spatial accuracy of better than 0.5 mm. However, small diameter probes sacrifice FOV for transverse resolution, which is a potential drawback of en face capsule technology [124].…”
Section: Capsulementioning
confidence: 99%
“…3,4 A distal motorized design allows for a reduced rotational distortion, accurate beam scanning, 5,6 and laser marking procedures. 7 However, wires of distal motors partially block the scanning area, producing image shadows. This issue might become critical when abnormal tissue is coincidentally blocked in the image.…”
Section: Introductionmentioning
confidence: 99%